2011
DOI: 10.1155/2011/784698
|View full text |Cite
|
Sign up to set email alerts
|

Apple Procyanidins Suppress Amyloidβ-Protein Aggregation

Abstract: Procyanidins (PCs) are major components of the apple polyphenols (APs). We previously reported that treatment with PC extended the mean lifespan of Caenorhabditis elegans (Sunagawa et al., 2011). In order to estimate the neuroprotective effects of PC, we investigated the antiaggregative activity of PC on amyloid β-protein (Aβ) aggregation, which is a pathological hallmark of Alzheimer's disease. We herein report that PC significantly suppressed Aβ42 aggregation and dissociated Aβ42 aggregates in a dose-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 41 publications
(51 reference statements)
2
18
0
Order By: Relevance
“…We recently demonstrated that PC from apples had Sir2-dependent anti-ageing effects in worms (Caenorhabditis elegans) [9] . Moreover, we demonstrated that PC suppressed amyloid- protein aggregation [14] . However, the preventative effects of AP intaking against aging phenomena caused by endogenous chronic oxidative stress remain to be fully evaluated.…”
mentioning
confidence: 74%
“…We recently demonstrated that PC from apples had Sir2-dependent anti-ageing effects in worms (Caenorhabditis elegans) [9] . Moreover, we demonstrated that PC suppressed amyloid- protein aggregation [14] . However, the preventative effects of AP intaking against aging phenomena caused by endogenous chronic oxidative stress remain to be fully evaluated.…”
mentioning
confidence: 74%
“…Specific apple fractions and phytochemicals have been shown to extend the mean lifespan of C. elegans and Drosophila melanogaster, and to suppress amyloid-beta protein aggregation in C. elegans (Sunagawa et al 2011; Peng et al 2011; Toda et al 2011). For example, Sunagawa and coworkers showed that procyanidins from Fuji apples extended the mean lifespan of wild-type C. elegans by 12.1%, an effect that depended on SIR-2, a member of the sirtuin family of NAD+-dependent protein deacetylases.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with data from Toda et al . () where procyanidins (compounds also present in guarana) were potent suppressor of Aβ aggregation, able to suppress Aβ42 aggregation and dissociated Aβ42 aggregates in a dose‐dependent manner. In general, other natural polyphenols have been shown to act on different amyloidogenic proteins by inhibiting amyloid formation (Ferreira et al ., ).…”
Section: Discussionmentioning
confidence: 99%